(untitled) (ResearchJet Journal of Analysis and Inventions, 2020)
The article explores a number of theories about the need for state regulation of the economy. Sectoral and regional features of state regulation of the food market are revealed. The direction of state regulation of the food market is analyzed. Scientific conclusions are given regarding the improvement of mechanisms of state regulation of the food market.